Pernikahan Endogami Jemaat Ahmadiyah Yogyakarta Perspektif Maqashid Al-Shari'ah - Sahrul Hidayatullah (State Islamic University (UIN) of Sunan Ampel, 2022)
Abstrack : The marriage rule in the form of a prohibition on marrying someone other than Ahmadiyah (endogamy) is a special regulation regulated in an institution called Rishta Nata. The regulation is oriented towards maintaining the family in order to form a uniform view of life in the household of the Ahmadiyah congregation, so as to create a happy family harmony under the auspices of the Ahmadiyya teachings. This study will examine the endogamous marriage regulation system in the Ahmadiyya congregation, the aim is to analyze the function of the rules in the family and community scope of the Ahmadiyya Jama'at in Yogyakarta. This research is a field research which also includes qualitative with a phenomenological-sociological approach that uses the theory of Maqāṣid al-Sharī'ah Jamaluddin Athiyah. The conclusion of this study is that the Ahmadiyya Jamaat's endogamous marriage in the family dimension according to the maqāṣid al-sharī'ah Jamaluddin Athiyah can be understood from the seven spaces of movement as follows; First, maintain the pattern of relationships between husband and wife. Second, preserving the existence and purity of the Ahmadiyya Community. Third, maintain the peace and integrity of the family of the Ahmadiyya Community. Fourth, maintain the purity of the family lineage. Fifth, preserving the ideology of the Ahmadiyya Community in the family environment. Sixth, maintain the principles and patterns of family relationships. Seventh, protecting family economic disparities and alleviating poverty. Abstrak : Aturan pernikahan yang berupa larangan menikah dengan selain Ahmadiyah (endogami) merupakan peraturan khusus yang diatur dalam sebuah lembaga yang bernama Rishta Nata. Aturan tersebut berorientasi pada pemeliharaan keluarga agar terbentuk keseragaman pandangan hidup dalam rumah tangga jemaat Ahmadiyah, sehingga tercipta keluarga yang harmonis dibawah naungan ajaran Ahmadiyah. Penelitian ini akan mengkaji tentang sistem peraturan pernikahan endogami di jemaat Ahmadiyah, tujuannya untuk menganalisa fungsi aturan dalam ruang lingkup keluarga dan komunitas Jemaat Ahmadiyah di Yogyakarta. Penelitian ini merupakan penelitian field research yang juga termasuk kualitatif dengan pendekatan fenomenologis-sosiologis yang menggunakan teori Maqāṣid al-Sharī’ah Jamaluddin Athiyah. Kesimpulan dari penelitian ini adalah pernikahan endogami Jemaat Ahmadiyah dalam dimensi keluarga menurut maqāṣid al-sharī’ah Jamaluddin Athiyah dapat dipahami dari tujuh ruang gerak sebagai berikut; Pertama, menjaga pola hubungan antar suami-istri. Kedua, melestarikan eksistensi dan kemurnian Jemaat Ahmadiyah. Ketiga, menjaga ketentraman dan keutuhan keluarga Jemaat Ahmadiyah. Keempat, memelihara kemurnian nasab keluarga. Kelima, melestarikan ideologi Jemaat Ahmadiyah di lingkungan keluarga. Keenam, menjaga prinsip dan pola hubungan keluarga. Ketujuh, melindungi kesenjangan ekonomi keluarga serta mengentaskan kemiskinan.